Back to the sea: secondary marine organisms from a biogeographical perspective - PROCHEŞ, ŞERBAN (Biological journal of the Linnean Society, 2001)
Secondary marine organisms belong to groups of terrestrial ancestry which have recolonized marine habitats. Some of them are, to various degrees, still dependent on the terrestrial habitat where they originated, which imposes certain limits in the expansion of their distribution range. This makes them an ideal subject for historical reconstruction. Here I perform biogeographical analyses on the global distribution of 12 groups of land‐dependent secondary marine plants and animals (mangrove trees, sea turtles, sea snakes, seabirds and seals). When all groups are taken together, species diversity shows a unique bimodal pattern for each hemisphere, with high values in cold‐temperate and tropical regions, but low values in mid‐latitude regions. None of the individual groups considered reaches its highest species concentration in mid‐latitude regions. This is shown to be due to the existence of three different species assemblages, inhabiting the three species‐rich latitudinal bands (northern cold‐temperate, tropical, and southern cold‐temperate), and intermixing to a limited degree in the species‐poor mid‐latitude bands. This is evidence that secondary marine organisms diversified independently in cold‐temperate and tropical regions, and strongly suggests that colonization from terrestrial habitats took place independently in the three species‐rich latitudinal bands. Different constraints in the terrestrial habitat of origin are put forward as evolutionary incentives for colonizing the sea: glaciation processes in cold regions and competition in tropical regions.